Major trends in knowledge management research: a bibliometric study - Akhavan, P.; Ale Ebrahim, N.; Fetrati, M.A.; Pezeshkan, A. (Kluwer (now part of Springer), 2016)
This study provides an overview of the knowledge management literature from 1980 through 2014. We employ bibliometric and text mining analyses on a sample of 500 most cited articles to examine the impact of factors such as number of authors, references, pages, and keywords on the number of citations that they received. We also investigate major trends in knowledge management literature including the contribution of different countries, variations across publication years, and identifying active research areas and major journal outlets. Our study serves as a resource for future studies by shedding light on how trends in knowledge management research have evolved over time and demonstrating the characteristics of the most cited articles in this literature. Specifically, our results reveal that the most cited articles are from United States and United Kingdom. The most prolific year in terms of the number of published articles is 2009 and in terms of the number of citations is 2012. We also found a positive relationship between the number of publications’ keywords, references, and pages and the number of citations that they have received. Finally, the Journal of Knowledge Management has the largest share in publishing the most cited articles in this field.